State-business relations in contemporary China: the case of the ‘Chinese Football Dream’ reforms - Ross, Tobias (2024)
State-business relations play a crucial role in China’s economic development and policy implementation. Characterised by an asymmetric dependency nexus, local government officials court business investments to facilitate policy and boost their political careers, while private firms are increasingly incentivised to support party-state goals to navigate their business through the political economy. The ‘Chinese Football Dream’ reforms launched in 2014 resemble such a party-state goal, exhibiting how private business actors and government officials have been willing to exchange economic and political resources for their personal, economic, or political gain. By taking the national reform policy as a case study, this study aims to explore and understand the dynamics and implications of football-related Corporate Political Strategy within the context of China’s political economy under Xi Jinping. As its theoretical framework the study is drawing on an integrated combination of Resource Dependence Theory and Corporate Political Strategy, including a specially adapted local typology of the latter. By using insights from 61 semi-structured interviews with practitioners, supported by publicly available micro and macro-economic industry data, the study provides a rare inside-view investigating the extent, types, determinants, and outcomes of football-related Corporate Political Strategies and their exchanges within the ‘Chinese Football Dream.’ The study argues that the expansion of China’s football industry from 2014-2020 was predominantly driven by private investors employing Corporate Political Strategies. The strategies’ investments primarily follow political calculi, and only secondary, if at all, any economic logics. Variations in strategy determinants lead to diverse strategies and outcomes, in part explaining the high volatility experienced among professional clubs, but generally argue for a case and context-specific examination. Clubs’ sporting success here shows a positive correlation with the probability and magnitude of obtaining benefits, a trend observed among both investors and governments, with stronger correlation in areas with less football development. Conversely, for clubs emblematic of the local city, the experience of sporting failure can have adverse effects on involved investors and governments. In addition to contributing novel perspectives into all three sub-domains of Corporate Political Strategy research (typologies, determinants, and outcomes), the study adds to the understanding of the modus operandi of private business and local government within the shifting political economy under Xi Jinping, as well as the broader fields of sports and football in Asia and state-regulated countries.